The Interplay of Gender and Turn-Taking Dynamics in English as a Lingua Franca Group Discussions - Atta, Habiba (2025)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Habiba Atta entitled, “The Interplay of Gender and Turn-Taking Dynamics in English as a Lingua Franca Group Discussions”, submitted in December 2025. Thesis advisor is Dr. Adnan Ajsic and thess co-advisor is Dr. Ozgur Parlak. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).